Genome-wide analysis of NAC transcription factors and their response to abiotic stress in celery (Apium graveolens L.). (February 2020) - Duan, Ao-Qi; Yang, Xiao-Lan; Feng, Kai; Liu, Jie-Xia; Xu, Zhi-Sheng; Xiong, Ai-Sheng
Graphical abstract: Highlights: A total of 111 putative NAC TFs were found and identified based on celery transcriptome and genome database. The AgNAC TFs were classified into 18 subfamilies and their physicochemical properties were preliminary analyzed. Expression profiles of selected AgNAC genes in response to abiotic stress were detected. Abstract: In plants, NAC (NAM, ATAF, CUC) is a class of transcription factors (TFs) involved in growth regulation and is associated with abiotic stress, morphogenesis, and metabolism. Celery ( Apium graveolens L.) is an important leafy vegetable and its yield and quality are considerably influenced by environmental factors. Currently, the characterization of NAC genes in celery is still limited. In this study, a total of 111 putative NAC TFs were determined based on the celery transcriptome and genome database. They were divided into 18 subfamilies on the basis of their NAC domain. NAC TFs in celery account for a moderate number compared with other species, similar to that in carrot. Real-time quantitative PCR (RT-qPCR) showed that some AgNAC genes were differentially expressed under adverse conditions (heat, cold, drought, and salt). AgNAC63 (ortholog of ANAC072 / RD26 ) was highly induced by heat, cold, and salt conditions. The expression levels of AgNAC47 in leaf blades were 105.25- and 123.14-fold those of petioles and roots, respectively. AgNAC63 and AgNAC47 showed significant tissue specificity, high expression in leaves, and varying degrees of response under the four treatments. This study provides a basis for the improved investigation of the structure and function of AgNAC TFs and celery stress resistance.